Intervention strategies for the safe use of semi-treated wastewater by Iranian farmers: An approach for safe food production in the circular economy - Sasan Esfandiari Bahraseman; Ali Firoozzare; Tinoush Jamali Jaghdani; Arash Dourandish (NJAS: Impact in Agricultural and Life Sciences, 2024)
The safe use of wastewater in irrigation practices in developing countries, and especially regions with water shortages, is an issue of concern for policymakers and society at large as the unsafe use of treated or semi-treated wastewater can pose potential risks to the environment, the safety of agricultural products and ultimately food safety. The implementation of supplementary parameters surrounding irrigation conditions with treated or semi-treated wastewater at the farm level depends on the behaviours of farmers, with psychological factors coming into play. Furthermore, accurate intervention strategies can guide farmers towards the safe usage of wastewater for irrigation. In this study, we have used survey data from Mashhad County in Iran to test the components of the theory of planned behaviour, including the effects of two intervention strategies, namely government enforcement and cooperative involvement, on farmers' safety behaviours when it comes to using semi-treated wastewater for irrigation practices. Structural equation modelling was employed for the analysis. The results show that the three key components of the theory of planned behaviour, that is attitude, subjective norms, and perceived behavioural control, have a significant impact on the intentions of farmers to engage in the safe use of semi-treated wastewater for irrigation. Additionally, cooperative involvement is more effective for the farmers than government enforcement. This suggests that there should be an increase in the official support available for agricultural cooperatives that operate as wastewater collectives.
Keywords: 630; agri-product safety; municipal wastewater treatment; theory of planned behaviour; irrigation; cooperatives